2013
DOI: 10.7897/2230-8407.04713
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Rational Prescribers Through the Pharmacology and Therapeutics Course Work of MBBS Syllabus in Bangladesh

Abstract: Pharmacology is most rapidly expanding science in medical discipline which leads to the development of many important drugs to treat many medical conditions that was previously untreatable. This paper focuses on the necessity of integration of pharmacology in the medical curriculum in all clinical phases and ethical aspects of medicine in terms of irrational prescribing. Irrational prescribing of drugs is a major global health problem in medical practice. Currently Pharmacology is taught at phase-II, a 2 year … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Not the least of these is the 'therapeutic jungle', the term used to refer to the combination of the overwhelming number of drugs, the confusion over nomenclature and the associated uncertainty of the status of many of these drugs" (Gilman et al, 1985). The situation also exist in Bangladesh as there are more than 1100 generics and every year 50 to 60 new drug molecule is entering country's drug market (Salam et al, 2013). Thus 'drug explosion' also exist in least developed country like Bangladesh (McGettigan et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Not the least of these is the 'therapeutic jungle', the term used to refer to the combination of the overwhelming number of drugs, the confusion over nomenclature and the associated uncertainty of the status of many of these drugs" (Gilman et al, 1985). The situation also exist in Bangladesh as there are more than 1100 generics and every year 50 to 60 new drug molecule is entering country's drug market (Salam et al, 2013). Thus 'drug explosion' also exist in least developed country like Bangladesh (McGettigan et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…At many occasion these concept are quite complicated in early years of medical school. Henceforth, modern countries and in some neighbouring countries of Bangladesh has adopted newer more updated teaching methods with more clinical orientation and therapeutics and integration of curriculum to ensure more interest and effective teaching and learning (Michel et al, 2002;Flockhart et al, 2002;Orme et al, 2002;Vollebregt et al, 2006;MCI, 1997;Shankar et al, 2005;Aronson et al, 2006). These methods have significantly changed the situation of drug use.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that Azar Hospital, Golestan University of Medical Sciences 69% (220 cases of 318 admitted patients) had received antibiotics in internal, infectious disease, and surgical wards and ICUs [57]. Same study and several other studies conveyed that irrational prescription of medicine including antimicrobials possibly will result in poor health status and enormous financial impact for any community or country [57][58][59][60][61]. Antimicrobials alone took the share 30-50% of all prescribed medicine in quite a lot of countries [58,62].…”
Section: The Islamic Republic Of Iranmentioning
confidence: 99%
“…Multiple studies have reported that following guidelines promotes prudent and rational use of not only antibiotics, but also overall medication [16][17][18][19][20][21][22]. Special care should be taken regarding antimicrobial resistance, which is a global public health problem [23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%